VALIDITAS DAN PRAKTIKALITAS E-MODULE BERBASISI INKUIRI TERBIMBING YANG DISERTAI LABORATORIUM VIRTUAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Cartika Candra Ledoh; Agustina Simorangkir; Nurbaya; Suriyah Satar; Hanida Listiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to evaluate the validity and practicality of e-modules based on inkuiri, which are complemented by virtual laboratories in the research materials to increase the critical thinking skills of SMA students. This type of research is called research and development (R&D) and it follows the Borg and Gall model, which breaks down several phases into three main stages: research, development, and research. The research instrument is a validation tool used by researchers and practitioners using the Likert scale. The analysis's results indicate that the penilaian scores are in the right category, with the highest scores coming from the categories of material (3,50), media (3,85), bahasa (3,75), and analysis (3,65). Based on the validity and practicality tests, it is concluded that the e-modules are both valid and practical to use.